Building Science Teachers' Conceptual Understanding with PhET Simulation - Tuhurima, David; Batlolona, John Rafafy (Unram Journal of Community Service, 2025)
This community service activity aims to improve the knowledge and skills of science teachers in creating practical simulation media using the PhET application. Involving 12 teachers, this training focused on creating practical simulation media that can be implemented in the learning process. The main results of this activity showed a significant increase in teachers' understanding and skills in managing learning media, as reflected in the positive response of participants to the use of PhET Simulation. In addition, teachers succeeded in producing simulation media that were relevant to the teaching material, increasing students' creativity and interest in science lessons. The main conclusion of this activity is that the integration of PhET Simulation in learning can deepen students' conceptual understanding and improve the quality of education at SMP Kristen 1 Dobo as a whole. This program also opens opportunities for further development in the use of educational technology in remote areas such as the Aru Islands.